The Venom of Spectacled Cobra (Elapidae: Naja naja): In Vitro Study from Distinct Geographical Origins in Sri Lanka - Duminda S. B. Dissanayake; Lasanthika D. Thewarage; Roshitha N. Waduge; J. G. S. Ranasinghe; S. A. M. Kularatne; R. P. V. Jayanthe Rajapakse (Journal of Toxicology)
Several countries residing envenomation due to Naja naja had revealed a disparity in the venom composition according to their geographic location and Sri Lankan cobra still lacks the evidence to support this. Therefore, the current study was focused on addressing relationship between the histopathological changes according to geographic variation of Sri Lankan N. naja venom. The histopathological changes in vital organs and muscle tissues following intramuscular administration of venom of N. naja were studied using BALB/c mice. The median lethal dose of venom of N. naja in the present study was determined to be 0.55, 0.66, 0.68, 0.62, and 0.7 mg/kg for North (NRP), Central (CRP), Western, Southern, and Sabaragamuwa Regional Population venoms, respectively. Histopathological changes were observed in different levels in vital organs and muscle tissues of mice. NRP accompanied significantly higher infiltration of inflammatory and necrotic cells into skeletal muscle and CRP venom demonstrated high level of cardiotoxic effects comparing to other regions. This study revealed a certain extent of variations in the pathological effects of N. naja venom samples according to their geographical distribution.